The Peculiarities of Physical Literacy Assessment in Primary School Students (Laisvalaikio tyrimai, 2023)
Over the last decade, academics, professionals, and politicians have become increasingly interested in the assessment of children’s and adolescents' physical literacy in physical education. Physical literacy has been measured and quantified as a multidimensional term comprising behavioral, psychological, and physical components. The majority of this research was conducted on children and adolescents in educational settings, emphasizing the importance of this age group in establishing the foundations of physical literacy, which will influence lifetime physical activity, health, and well-being. Since there are no studies in the population of Lithuanian primary school students, evaluating children's physical literacy or the validity and reliability of individual physical literacy assessment instruments, the current overview may be useful in guiding the development of future research in this area in our country.The objective of this study is to review the assessment of physical literacy in primary school children from a theoretical standpoint.Methods: analysis of scientific literature and assessment instruments for physical literacy.Conclusions:1. There is no consensus on the assessment of children's physical literacy. Representatives of the idealistic approach suggest using subjective, qualitative, and interpretive methods to monitor a student’s progress on their individual path to physical literacy. Supporters of the pragmatic approach view physical literacy as the result of practical activities that must be measured and assessed using instruments to evaluate fundamental movement skills, physical fitness, motivation, etc.Physical literacy in primary school students could be assessed across four domains: affective, behavioral, cognitive, and physical. The affective part of the assessment tools for elementary school children is indicated by the child's motivation and self-confidence. The behavioral part is reflected by the child's objective physical activity, subjective physical activity, variety and frequency of physical activities, and participation in physical activities in different places and at different times of the year. The cognitive part is shown by the child's knowledge of physical activity and the benefits of taking part in physical activities, as well as by the child's understanding of how to plan and carry out physical activities. The physical part is demonstrated by physical fitness, movement skills, and self-perceived competence.Keywords: physical literacy, primary school students, assessment.